Present and future of the tecnnology GPS (Global Positioning System) in the Geodynamic Applications in Colombia - Mora-Páez, Héctor (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
Since 1988, Ingeominas has been using the GPS technology as a component of the geodynamic phenomena's study. The experience gained during several years of field work forr GPS data collection, processing and interpretation, gave rise the need to make and additional effrot to implemenr a National Wide GPS Permanent Network that will contribute to the geodynamic phenomena's understanding, especially that one related to seismic and volcanic deformation. This document presents some general aspects, about the GPS technology's current situation and its future use with that purpose; technology wich has been used successfully in many countries, in the development of the research programs oriented to the disasters prevention.